Peningkatan Keaktifan dan Hasil Belajar PPKn melalui Discovery Learning Berbantuan Aplikasi Wordwall Games - Puspitarini, Dyah (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to improve student activity and learning outcomes through the application of a discovery learning model assisted by a wordwall game application in the national integration material for class X MIPA-1 SMA Negeri 5 Yogyakarta in the 2021/2022 academic year. This classroom action research was carried out in two cycles. Collecting data through observation and documentation, analyzed by calculating the percentage increase in the value of activeness and the percentage increase in learning outcomes, then interpreted and compared with indicators of success. The results showed that the discovery learning model assisted by the wordwall game application could increase student activity and learning outcomes. The value of activity in the first cycle was 61.92% to 74.31% in the second cycle (an increase of 12.39%). Individual activity in the medium-high category from 66.67 % in the first cycle to 89.89% in the second cycle (an increase of 23.22%). The learning outcomes of the knowledge aspect in the first cycle have an average value of 74.44, to 87.30 in the second cycle (an increase of 12.86). The number of students who completed the first cycle was 19 students (52.78%) and in the second cycle as many as 30 students (83.33%), an increase of 30,55%. The learning outcomes in the very good category of skills increased from 3 students (8.33%) in the first cycle to 9 students (25%) in the second cycle. While the learning outcomes of the attitude aspect did not change drastically, some students showed an increase in behavior in the aspects of order and obedience to the rules, so the value of the very good category increased from 6 students (16.67%) in cycle 1 to 10 students (27.78 %) in cycle 2.